The very hungry caterpillar - Carle, Eric (World of Eric Carle., 1987)
Follows the progress of a hungry little caterpillar as he eats his way through a varied and very large quantity of food until, full at last, he forms a cocoon around himself and goes to sleep and wakes up a butterfly --